Current Percolation in Medium with Boundaries under Quantum Hall Effect Conditions - M. U. Malakeeva; V. E. Arkhincheev (Advances in Condensed Matter Physics)
The current percolation has been considered in the medium with boundaries under quantum Hall effect conditions. It has been shown that in that case the effective Hall conductivity has a nonzero value due to percolation of the Hall current through the finite number of singular points (in our model these are corners at the phase joints).